Political journalistic temporalities: an analytical approach - Faure, Antoine (Re-presentaciones: Periodismo, comunicación y sociedad, 2018)
Our purpose is to present the theoretical approach of a research project in History, about Chilean Journalism. The contribution relies on an object that articulates individual, social, cultural and practical characteristics of journalism: i. e. journalistic temporalities. The question opens up new perspectives: the evolution of temporal routines and culture of Chilean journalists; and, the political meaning of those temporal changes in the profession. To detail this project, we introduce the way in which this problematic appeared, and the theoretical perspectives that open up the question of temporalities, specifically in a social high speed era
Keywords: Journalism; Pluralism; Historicity; Practices; Culture; Discourse; Temporalities